Cost of treatment in patients with metastatic soft tissue sarcoma who respond favourably to chemotherpy. The SArcoma treatment and Burden of Illness in North America and Europe (SABINE) study. (28th April 2015) - Jönsson, L.; Justo, N.; Musayev, A.; Krishna, A.; Burke, T.; Pellissier, J.; Judson, I.; Staddon, A.; Blay, J.Y.
Abstract : Treatment of metastatic soft tissue sarcoma (mSTS) commonly includes multiple lines of chemotherapy, until a decline in performance status precludes further treatment. The primary objective of this study was to describe the lifetime healthcare resource utilisation and cost among mSTS patients with favourable response to chemotherapy. SABINE was a multi‐centre ( n  = 25), multi‐country ( n  = 9) retrospective chart review study of mSTS patients with favourable response to chemotherapy following 4 cycles. Healthcare resource utilisation was collected from first line until death or end of follow‐up. Costs were analysed by health states (defined by treatment line, chemotherapy use and disease progression) and estimated by multiplying the mean weekly cost per health state by the expected number of weeks spent in each health state. Expected per‐patient lifetime medical cost was €65 616 (95% CI: €51 454–€85 003); comprised of IV chemotherapy (31.7%), inpatient care (24.8%), concomitant medication (11.0%), oral chemotherapy (8.9%), outpatient visits (8.8%), radiotherapy (6.3%), hospice (4.0%), imaging (3.7%) and laboratory (0.7%). Weekly costs were 280–330% higher during chemotherapy treatment periods than off‐chemotherapy, especially after disease progression. Per‐patient costs were highest in the USA and lowest in the Netherlands and UK. The economic burden of mSTS is considerable and the amount of resources devoted to its treatment varies across countries.